Determinants of Off-farm Activity Participation among Cotton Farmers in Punjab, Pakistan - Muhammad Iqbal; Qing Ping; Umar Ahmed; Adnan Nazir (International Journal of Management, Accounting and Economics, 2015)
The study was conducted to determine the aspect affecting the farmer in taking part in off-farm activities in three cotton growing districts of Punjab province, Pakistan. Since off-farm activities have become an imperative part of income strategies among rural families in developing countries like Pakistan. The data was documented from a total of 180 cotton farmers using multistage cluster sampling technique. A binary logistic model was used to evaluate the determinants motivating the farmers to participate in different off-farm activities. Various socio-economic factors were found significantly associated with probability of immersion in non-farm activities. The results of the model reveal different factors like total farming area and farmers having access to road were significant for several business activities through odds ratio 1.051 and 0.088 respectively. Though more experienced farmers with odds ratio (1.063) had more likelihood for labour activities. Lastly more educated farmers and large family size have higher probability to go for services type of off-farm activities and their odds ratio estimated is 1.297, 2.069. These findings have essential implications for policy, economic growth and development.